Health promotion in Spanish social policies according to the 2030 Agenda - Alandí Palanca, Marta; Ortega Navas, María del Carmen; García Pérez, María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
At the dawn of the 21st century, it is necessary to promote social policies that enhance Health Education, in line with the United Nations 2030 Agenda. We have proceeded to compare the social policies related to Health Education enacted in Spanish territories according to some goals established in the 2030 Agenda. Through a comparative analysis with the Atlas.ti version 22 software, the results have been obtained, showing that social policies are undergoing a transformation but with differences. It is observed that political commitments backed by regulations that accompany them are increasingly necessary.